drivers of Africa’s agriculture transformation: A CAADP biennial review account - Benin, Samuel (International Food Policy Research Institute, 2021)
This paper assesses the nature of agricultural transformation taking place in different parts of Africa and analyzes drivers of the transformation using data from the CAADP Biennial Review (BR) on 46 indicators from 2014 to 2018. First, a typology of agriculture transformation in different groups of countries is developed by analyzing the initial values and trends in three indicators—share of agriculture in total employment, share of agriculture in gross domestic product, and agriculture labor productivity. The typology, in addition to a conceptual framework that is developed for measuring the relative effect of a on an outcome, provides the basis for analyzing the drivers of agriculture transformation. The 46 BR indicators are classified into policies (13 indicators), intermediate results (23 indicators), and outcomes (10 indicators), and then econometric methods are used to measure the association between the indicators and the intermediate results and outcomes, which include agriculture intensification (e.g., access to finance and extension, fertilizer use, and irrigation development), agriculture growth, agriculture trade, food security, nutrition, and poverty. Different fixed-effects regression methods and model specifications of the explanatory variables are used to assess sensitivity of the results to different assumptions of the data and the relationship between the policies and intermediate and outcome indicators. The trends in the indicators are different. For example, access to finance and extension have risen over time; fertilizer use, irrigation development, agriculture growth, and adult undernourishment have fallen over time; and child nutrition and poverty have remained stagnant over time. Different indicators are significantly associated with different indicators of agriculture intensification, agriculture growth, and outcomes. Also, there are differences in the results across the agriculture transformation groups. Major drivers of agriculture transformation in the different groups are identified. Implications of the results and suggestions for future research are discussed.